Nimodipine fosters remyelination in a mouse model of multiple sclerosis and induces microglia-specific apoptosis - Schampel, Andrea; Volovitch, Oleg; Koeniger, Tobias; Scholz, Claus-Juergen; Joerge, Stefanie; Linker, Ralf; Wischmeyer, Erhard; Wunsch, Marie; Hell, Johannes W.; Erguen, Sueleyman; Kuerten, Stefanie (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Despite continuous interest in multiple sclerosis (MS) research, there is still a lack of neuroprotective strategies, because the main focus has remained on modulating the immune response. Here we performed in-depth analysis of neurodegeneration in experimental autoimmune encephalomyelitis (EAE) and in in vitro studies regarding the effect of the well-established L-type calcium channel antagonist nimodipine. Nimodipine treatment attenuated clinical EAE and spinal cord degeneration and promoted remyelination. Surprisingly, we observed calcium channel-independent effects on microglia, resulting in apoptosis. These effects were cell-type specific and irrespective of microglia polarization. Apoptosis was accompanied by decreased levels of nitric oxide (NO) and inducible NO synthase (iNOS) in cell culture as well as decreased iNOS and reactive oxygen species levels in EAE. In addition, increased numbers of Olig2(+)APC(+) oligodendrocytes were detected. Overall, nimodipine application seems to generate a favorable environment for regenerative processes and therefore could be a treatment option for MS, because it combines features of immunomodulation with beneficial effects on neuroregeneration.
EVALuna2:22492